Identification of the Causes of Defects in the Process of Making Salted Soy Sauce at CV. Indococo Pacific - Dian Novitasari; Mukhlis Fauzi Utomo (Indonesian Journal of Food Technology, 2022)
Indococo Pacific in carrying out the soy sauce production process needs to implement quality control in order to produce products with good quality. Based on this, this research was conducted with the aim of (1) analyzing product defects in the soy sauce production process and (2) identifying possible causes of problems. The research data is primary data from observations and interviews with management. The data obtained were analyzed using a p control chart and a fishbone diagram. The results showed that the damage occurred due to sluggish product packaging and the level of damage was still within tolerance limits. The damage was caused by factors: human, material, methodology, and the environment.